The evolution of a spot–spot-type solar active region which produced a major solar eruption - Liu, Lijuan (Frontiers in Astronomy and Space Sciences, 2023)
Solar active regions (ARs) are the main sources of large solar flares and coronal mass ejections. It is found that the ARs producing large eruptions usually show compact, highly-sheared polarity inversion lines (PILs). A scenario named as “collisional-shearing” is proposed to explain the formation of this type of PILs and the subsequent eruptions, which stresses the role of collision and shearing induced by relative motions of different bipoles in their emergence. However, in observations, if not considering the evolution stage of the ARs, about one third of the ARs that produce large solar eruptions govern a spot-spot type configuration. In this work, we studied the full evolution of an emerging AR, which owned a spot-spot type configuration when producing a major eruption, to explore the possible evolution gap between “collisional shearing” process in flux emergence and the formation of the spot-spot type, eruption-producing AR. We tracked the AR from the very beginning of its emergence until it produced the first major eruption. It was found that the AR was formed through three bipoles emerged sequentially. The bipoles were arranged in parallel on the photosphere, shown as two clusters of sunspots with opposite-sign polarities, so that the AR exhibited an overall large bipole configuration. In the fast emergence phase of the AR, the shearing gradually occurred due to the proper motions of the polarities, but no significant collision occurred due to the parallel arrangement of the bipoles. Nor did the large eruption occur. After the fast emergence phase, one large positive polarity started to show signs of decay. Its dispersion led to the collision to a negative polarity which belonged to another bipole. A huge hot channel spanning the entire AR was formed through precursor flarings around the collision region. The hot channel erupted later, accompanied by an M7.3-class flare. The results suggest that in the spot-spot type AR, along with the shearing induced by the proper motions of the polarities, a decay process may lead to the collision of the polarities, driving the subsequent eruptions.